ANALISIS PERUBAHAN DALAM TATA CARA PERKAWINAN MASYARAKAT ADAT BATAK TOBA PADA MASYARAKAT PERANTAUAN DI KOTA PEKANBARU - Tindaon, Nova Kristiani; Hambali, Hambali; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by a change in the marriage procedures ofthe Toba Batak indigenous people to overseas communities in the city of Pekanbaru.The formulation of the problem in this research is what aspects of the Batak Tobatraditional marriage procedures have changed in the overseas Toba Batak communityin Pekanbaru City and what are the factors that affect changes in the Batak Tobatraditional marriage procedures in Pekanbaru. The purpose of this study is to analyzethe changes in aspects of the Batak Toba traditional marriage procedures in the BatakPerantau community in Pekanbaru City and determine the factors that influencechanges in the Batak Toba traditional marriage procedure in the Batak Perantaucommunity in the city of Pekanbaru. The data collection techniques in the study areobservation, interviews, and documentation. The number of informants in this studyamounted to 5 (five) people, 1 (one) of whom was the leader of the Toba Batak adat, 1(one) religious leader, and 3 (three) others were lay people. While the data that hasbeen obtained are analyzed by data reduction, data presentation and conclusiondrawing. After the data is collected and analyzed and tested using the data validity test,the dependability test, and the confirmability test, there is a change in the marriageprocedure there is a Toba Batak Overseas in the city of Pekanbaru. The aspects thatexperienced changes or shifts in the customs of Batak Toba marriages in Batak Tobacommunities in the city of Pekanbaru are aspects of mangaririt, marhusip, marhatasinamot, martonggo raja or marria raja, martumpol, manganese inland, manjalotumpak, mambagi parjambaron, mangalehon ulos parboru, paulak une and steppingdown the stairs. While the factors that dominate the change in the procedure of BatakToba traditional marriages in the Batak indigenous people overseas in the city ofPekanbaru are discovery or new, and supported by the factor of invention orrecognition and acceptance of new discoveries, innovation or adjustment, diffusion orspread of cultural elements, acculturation or the meeting of two or more culturalelements, and the penetration or acceptance of a foreign culture.Key Words: Change, Marriage Procedures, Toba Batak.